Spinach analysis practical - Hoare, Peter (The University of Hull)
A comparison of the "freshness" of spinach using tlc - takes "typical" 6th form student ca. 1 - 1.5 hours to complete. Student instruction sheet and Technicians apparatus and chemicals list.